Barriers to Employment of Young Cultural Practitioners With Visual Impairments in the Cultural Industries of Ethiopia. (September 2022) - Yeshanew, Yisma Tsige
Introduction: Employment in the culture and arts sector has multiple psycho-socioeconomic benefits for people with visual impairments. However, a study in this area is rare in Ethiopia. The current study explored barriers to employment of young cultural practitioners with visual impairments in the cultural industries of Ethiopia.Method: Eight young cultural practitioners who have visual impairments were interviewed and the qualitative data were thematically analyzed.Results: The results indicated that personal, attitudinal, and environmental barriers hinder the meaningful participation of young cultural practitioners with visual impairments in the job market of the cultural industries of Ethiopia.Discussion: Although the study found differences in geographic and sectoral barriers to employment the results of the current study supported previous research findings.Implications: The current study has implications for future research as well as policymakers concerning employment and labor affairs. Besides highlighting the need for an increased understanding of identified barriers to cultural employment, the study revealed that there is also a need for further research on the numerous benefits that employment and participation in culture and arts provide for people with and without impairments at individual, community, and national levels.